2014
DOI: 10.1021/jp505301h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Global Charge of the Protein on the Stability of Lysozyme–AuNP Bioconjugates

Abstract: The relevant biological information to take into account the design of bionanoconjugates is the structural organization of the proteins that interact with a metallic nanoparticle and form a protein corona. We have studied the interaction of the protein lysozyme (LYZ) with gold nanoparticles (AuNPs) protected by citrate, 6-mercaptopurine, and ω-mercaptoundecanoic acid monolayers in aqueous solution in a wide pH range. The bioconjugates are stable at pH higher than the isoelectric point (pI) of LYZ. At lower pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…The result from fluorescence lifetime measurement clearly indicates the formation of ground-state complexation between lysozyme and TBO. Furthermore, the observed results from time-resolved fluorescence studies correlate well with results from steady state emission quenching experiments (64,68,69). Equations (5) and (6) K SV * (910 5 dm 3 mol 1 ) K q * (910 13…”
Section: Fluorescence Lifetime Measurementsupporting
confidence: 74%
“…The result from fluorescence lifetime measurement clearly indicates the formation of ground-state complexation between lysozyme and TBO. Furthermore, the observed results from time-resolved fluorescence studies correlate well with results from steady state emission quenching experiments (64,68,69). Equations (5) and (6) K SV * (910 5 dm 3 mol 1 ) K q * (910 13…”
Section: Fluorescence Lifetime Measurementsupporting
confidence: 74%
“…However, others have suggested that neither protein size nor charge significantly determine the protein fingerprints, confirming that electrostatic affinity alone does not constitute the major driving force regulating the silica-corona interactions. 41 …”
Section: Resultsmentioning
confidence: 99%
“…From the time-resolved fluorescence decay profiles of Lys in the absence and presence of chelerythrine (not shown) the fluorescence lifetime values and their amplitudes were calculated. [61][62][63] Steady-state fluorescence anisotropy study Steady state anisotropy data may provide valuable information on the degree of motional restriction of the fluorophore and is used as a probe to assess the extent of the flexibility or tumbling motion of small molecules after binding. After adding the maximum concentration of the chelerythrine iminium and alkanolamine forms (100 mM) to Lyz, the observed average fluorescence lifetime values were t = 1.81 ns and 2.07 ns, respectively.…”
Section: Fluorescence Lifetime Studymentioning
confidence: 99%